2011
DOI: 10.1111/j.1574-695x.2011.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of biofilm formation of methicillin-resistantStaphylococcus aureus(MRSA) strains from patients with orthopaedic device-related infections

Abstract: Biofilms play a pivotal role in medical device-related infections. However, epidemiological analysis of biofilm formation and genotyping among clinical methicillin-resistant Staphylococcus aureus (MRSA) isolates from patients with orthopaedic infections has rarely been reported. A total of 168 MRSA strains were examined: 23 strains from patients with device-related infection (the device group); 55 from patients with device-non-related infection (the nondevice group); and 90 from asymptomatic nasal carriers (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
(41 reference statements)
1
21
1
Order By: Relevance
“…A survey of biofi lm production among 26 staphylococcal isolates (13 S. aureus , 10 S. epidermidis , 1 S. hominis , 1 S. warneri , 1 S. lugdunensis ) recovered from 23 orthopedic devices noted that all the strains formed biofi lms and 19 (73.1 %) possessed the ica gene (Esteban et al 2010 ). Biofi lm production was also surveyed among 168 MRSA isolates (23 device-associated, 55 nondevice associated and 90 nasal carriage isolates) from 87 infected and 95 colonized outpatients (Kawamura et al 2011 ). This study found a greater intensity of biofi lm staining among isolates from orthopedic devices.…”
Section: Biofi Lms From Aerobic Grampositive and Gram-negative Bacteriamentioning
confidence: 99%
“…A survey of biofi lm production among 26 staphylococcal isolates (13 S. aureus , 10 S. epidermidis , 1 S. hominis , 1 S. warneri , 1 S. lugdunensis ) recovered from 23 orthopedic devices noted that all the strains formed biofi lms and 19 (73.1 %) possessed the ica gene (Esteban et al 2010 ). Biofi lm production was also surveyed among 168 MRSA isolates (23 device-associated, 55 nondevice associated and 90 nasal carriage isolates) from 87 infected and 95 colonized outpatients (Kawamura et al 2011 ). This study found a greater intensity of biofi lm staining among isolates from orthopedic devices.…”
Section: Biofi Lms From Aerobic Grampositive and Gram-negative Bacteriamentioning
confidence: 99%
“…There are different ways for evaluating biofilm formation ability such as: microtitre plate, a tube test, radiolabelling, Congo red agar plate test and confocal laser scanning microscopy. The most popular of them is crystal violet microtitre plate assay (17).…”
Section: Discussionmentioning
confidence: 99%
“…QS is encoded by the agr operon where agrD encodes the autoinducer. In a study of 168 strains of MRSA, 23 were from patients with device-related infections, 55 were from patients with non-device-related infections, and 90 were from asymptomatic nasal carriers (Kawamura et al, 2011). The device group had a significantly higher prevalence of agr-2 than the colonization group (78.3 % vs 34.4 %, P50.001) and a higher biofilm index compared to agr-1 and agr-3.…”
Section: Biofilms In Mrsa Infectionsmentioning
confidence: 99%